A novel CASR mutation (p.Glu757Lys) causing autosomal dominant hypocalcaemia type 1. (1st October 2018) - Kwan, Benjamin; Champion, Bernard; Boyages, Steven; Munns, Craig F; Clifton-Bligh, Roderick; Luxford, Catherine; Crawford, Bronwyn
Summary: Autosomal dominant hypocalcaemia type 1 (ADH1) is a rare familial disorder characterised by low serum calcium and low or inappropriately normal serum PTH. It is caused by activating CASR mutations, which produces a left-shift in the set point for extracellular calcium. We describe an Australian family with a novel heterozygous missense mutation in CASR causing ADH1. Mild neuromuscular symptoms (paraesthesia, carpopedal spasm) were present in most affected individuals and required treatment with calcium and calcitriol. Basal ganglia calcification was present in three out of four affected family members. This case highlights the importance of correctly identifying genetic causes of hypocalcaemia to allow for proper management and screening of family members. Learning points: ADH1 is a rare cause of hypoparathyroidism due to activating CASR mutations and is the mirror image of familial hypocalciuric hypercalcaemia. In patients with ADH1, symptoms of hypocalcaemia may be mild or absent. Basal ganglia calcification may be present in over a third of patients. CASR mutation analysis is required for diagnostic confirmation and to facilitate proper management, screening and genetic counselling of affected family members. Treatment with calcium and activated vitamin D analogues should be reserved for symptomatic individuals due to the risk of exacerbating hypercalciuria and its associated complications.